PATH-07. SIGNIFICANCE OF H3K4me3 IN PEDIATRIC HIGH-GRADE GLIOMAS. (9th November 2020) - Lewis, Rebecca; Wadhwani, Nitin; Mania-Farnell, Barbara; Tomita, Tadanori; James, Charles; Xi, Guifa
Abstract: Pediatric high-grade gliomas (pHGGs) account for ~20% of childhood brain tumors, are incurable in nearly all instances, and have an average patient survival of less than 15 months. Histone posttranslational modifications (PTMs) are deregulated in pHGGs. There are many gaps in our knowledge regarding the mechanisms by which "normal" PTM is subverted during pHGG development. Preliminary results from our lab show pHGGs are enriched in H3K4me3 and that the extent of this specific PTM is predictive of patient survival length. H3K4me3 levels are controlled by methyltransferase and demethylase activity. Gene expression analysis indicates SETD1A and WDR82, enzymatic subunits of human SETD1A containing methyltransferase complex (referred to as hSETD1A-COMPASS), are responsible for H3K4 methylation. SETD1A and WDR82 are significantly elevated in pHGGs, relative to pediatric low-grade gliomas (pLGGs), and both show a direct association with glioma malignancy. Interestingly, these associations do not exist in adult gliomas. The results suggest that hSETD1A-COMPASS specifically impacts pHGG development and is a potential therapeutic target for these tumors.